Clarification Regarding Marshall and Yates's Critique of "Dosage of Treatment to Sexual Offenders: Are We Overprescribing?" - Serin, Ralph C.; Looman, Jan; Malcolm, Bruce (International journal of offender therapy and comparative criminology, 2005)
The present article includes a response to recent criticisms leveled against an earlier article titled "Dosage of Treatment to Sexual Offenders: AreWe Overprescribing?" In that article, the authors argued that sexual offenders receiving low-intensity sex offender treatment in the Ontario Region of Correctional Service of Canada CSC may be receiving too many sex offender treatment programs. Marshall and Yates have argued that the analysis performed in that study was inappropriate and that, based on their re-analysis, the opposite conclusion may be more accurate. The present article discusses some of the assumptionsmade to Marshall and Yates in their article and presents recidivism data for individuals included in the earlier article. As well, the authors discuss additional information regarding treatment in the Ontario Region of CSC. The present article concludes that the points made in the earlier study were justified